(3xy-2ab)3_(3xy+2ab)³ simplify
Answers
Answered by
0
l didn't understand question
Answered by
2
Answer:
-108x²y²ab - 16a³b³
step by step explanation:
By using identity: a³- b³ = (a-b) (a²+b²+ab)
( 3xy - 2ab)³ - ( 3xy + 2ab )³
= { ( 3xy - 2ab ) - ( 3xy + 2ab ) } { ( 3xy - 2ab )² + ( 3xy + 2ab )² + ( 3xy - 2ab ) ( 3xy + 2ab ) }
= ( - 4ab ) ( 9x²y² + 4a²b² - 12abxy + 9x²y² + 4a²b² + 12abxy + 9x²y² - 4a²b² )
= ( - 4ab ) ( 27x²y² + 4a²b² )
= - 108x²y²ab - 16a³b³
This is the required answer.
Similar questions